2014
DOI: 10.5194/acp-14-6329-2014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the intensity changes of tropical cyclones over the western North Pacific

Abstract: Abstract. The influence of environmental conditions on the intensity changes of tropical cyclones (TCs) over the western North Pacific (WNP) is investigated through examination of 37 TCs during 2000-2011 that interacted directly with the western North Pacific subtropical high (WNPSH). Comprehensive composite analysis of the environmental conditions is performed for two stages of storms: one is categorized as intensifying events (maximum wind speed increases by 15 kn over 48 h) and the other is categorized as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…The greater tilting of the horizontal vorticity was a result of the correlation between upward motion and the horizontal vorticity due to the upper-tropospheric trough. From this perspective, the outcome of a TC-trough interaction depends not only on the size and strength of the PV associated with the trough, as stated by Hanley et al (2001), but also on the interaction between convection and the trough-induced shear as suggested by Shu et al (2014). This conclusion was also supported by sensitivity experiments in which AHW forecasts with perturbed initial conditions had greater MSLP changes in response to variability of the downshear convection than in response to variability of the upper-tropospheric trough.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The greater tilting of the horizontal vorticity was a result of the correlation between upward motion and the horizontal vorticity due to the upper-tropospheric trough. From this perspective, the outcome of a TC-trough interaction depends not only on the size and strength of the PV associated with the trough, as stated by Hanley et al (2001), but also on the interaction between convection and the trough-induced shear as suggested by Shu et al (2014). This conclusion was also supported by sensitivity experiments in which AHW forecasts with perturbed initial conditions had greater MSLP changes in response to variability of the downshear convection than in response to variability of the upper-tropospheric trough.…”
Section: Discussionmentioning
confidence: 97%
“…Oftentimes a moderately sheared environment stems from an upper-tropospheric trough in close proximity to a TC (e.g., Hanley et al 2001; Davis and Bosart 2002;Molinari et al 2006;Shu et al 2014). In a composite study of TC-trough interactions in the North Atlantic, Hanley et al (2001) found that TCs are more likely to intensify than weaken after interacting with uppertropospheric troughs.…”
Section: B Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Apart from looking at the magnitude of VWS, the direction of VWS has also found to be important for TC genesis and intensity. Some studies show that easterly shear is more favorable to TC intensification than westerly shear (Ritchie and Frank 2007, Zeng et al 2010, Shu et al 2014. The beta-induced northwesterly shear within the inner core of the TC could partly offset the easterly shear and thereby results in weaker VWS and favors TC intensification.…”
Section: Introductionmentioning
confidence: 99%